GMPS sources and control of contamination during processing (University Park, Pa. The Pennsylvania State University, 1994)
Describes proper food handling methods beginning with the receipt of materials and ending with the storage of finished products.
VHS
Writer/producer, Arnold S. Roseman.
Keywords: Food industry and trade |x Safety measures; Food handling; Food contamination -- Prevention